Blow up and lifespan of solutions for elastic membrane equation with delay - Benzahi M.; Zara A.; Boulaaras S.; Jan R.; Iqbal M. (Elsevier B.V., 2025)
The primary objective of this research is to examine a nonlinear elastic membrane equation incorporating delay and source terms within a bounded domain. We obtain sufficient conditions on the initial data and the involved functionals for which the energy of solutions with non positive initial energy as well as positive initial energy blow up in a finite-time. In addition, this research work provides estimates for the lifespan of these solutions. ? 2023 The Author(s)